Audyt wewnętrzny w systemie kontroli publicznej na podstawie przepisów ustawy o finansach publicznych - Dasek, Tomasz (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
Internal audit is a new institution. It was introduced just from January 1, 2002 and intially it was merely the from of implementation of Poland's obligations towards the European Union. The role of internal audit is to provide independent and objective assurance that an organisation's risk managment, govermance and internal control processes are operating effectively. The article presents the changes of definitions of internal audit which is regulated in Polish law and international standards IIA
Keywords: audyt; audyt wewnętrzny; kontrola; finanse publiczne